Spiral-scan atomic force microscopy: a constant linear velocity approach - Mahmood, Iskandar Al-Thani; Moheimani, S.O. Reza (2010)
This paper describes an alternative method to the widely-used raster-scan technique for Atomic Force Microscopy (AFM). In this method, the sample is scanned in a spiral pattern instead of the well established raster trajectory. A spiral pattern is produced by applying cosine and sine signals with slowly varying amplitudes to the x-axis and y-axis of an AFM scanner respectively. In order to ensure that the spiral trajectory travels at a constant linear velocity (CLV), frequency and amplitude of the input signals are varied simultaneously in a way that the linear velocity of the scanner is kept constant. Experimental results obtained by implementing the CLV spiral scan on a commercial AFM indicate that, compared with the raster-scan method, high-quality AFM images of equal area and pitch can be generated two times faster and using half of the total traveled distance.